The Role of Intellectual Agility in the Implementation of Transformative Leadership in Improving MSME Business Performance - Edward; Fitri Chairunnisa; Perdana Siregar, Ade (Dinasti International Journal of Digital Business Management, 2023)
The leadership factor determines an organization in achieving success. Improving an organization's business performance requires an innovative and creative leader, so leaders are expected to have good intellectuals carrying out their roles. The effectiveness of transformative leadership and increasing intellectual agility are expected to improve MSME business performance to positively impact the economy for themselves and employees and reduce poverty. The objectives of this study are (1) to analyze the effect of transformative leadership on MSME business performance; (2) to analyze the effect of transformative leadership on intellectual agility; (3) to analyze the influence of intellectual agility on the business performance of MSMEs; (4) analyze the role of intellectual agility in mediating the effect of transformative leadership on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the study show (1) that transformative leadership has a significant positive effect on MSME business performance; (2) transformative leadership shows a significant positive effect on intellectual agility; (3) intellectual agility shows a significant positive effect on MSME business performance; (4) intellectual agility as a mediating influence of transformative leadership shows a significant positive effect on MSME business performance